Theorizing colonial cinema : reframing production, circulation, and consumption of film in Asia - Kwon, Nayoung Aimee; Odagiri, Takushi; Baek, Moonim (New directions in national cinemas., 2022)
"Theorizing Colonial Cinema is a millennial retrospective on the entangled intimacy between film and colonialism from film's global inception to contemporary legacies in and of Asia. The volume engages new perspectives by asking how prior discussions on film form, theory, history, and ideology may be challenged by centering the colonial question rather than relegating it to the periphery. To that end, contributors begin by excavating little-known archives and perspectives from the colonies as a departure from a prevailing focus on Europe's imperial histories and archives about the colonies. The collection pinpoints various forms of devaluation and misrecognition both in and beyond the region that continue to relegate local voices to the margins. This pathbreaking study on global film history advances prior scholarship by bringing together an array of established and new interdisciplinary voices from film studies, Asian studies, and postcolonial studies to consider how the present is continually haunted by the colonial past"--